들깨 잎 추출물의 항산화 및 신경세포 보호작용 - 이종임; 진창배; 류재하; 조정숙 (대한약학회, 2008)
The leaves of Perilla frutescens Britt. var. japonica Hara (Labiatae) are often used in gourmet food in several Asian countries. Two kinds of perilla cultivars, Namcheon (NC) and Bora (BR), have been respectively developed in Korea by the pure line of ‘deulkkae’ from the local variety and by the cross of ‘deulkkae’ and ‘chajogi’. The present study evaluated and compared antioxidant and neuroprotective effects of the fractions prepared from the leaves of the two cultivars using cell-free bioassay systems and primary cultured rat cortical cells. We found that the spirit, chloroform, hexane and butanol fractions from NC and BR leaves inhibited lipid peroxidation initiated in rat brain homogenates by Fe²+ and L-ascorbic acid. In contrast, only the spirit and butanol fractions from both cultivars exhibited 1,1-diphenyl-2-picrylhydrazyl radical scavenging activity. Among the fractions tested, the butanol fractions from NC and BR leaves exhibited the most potent antioxidant properties, and the butanol fraction from BR was more potent than the NC fraction. In consistence with these findings, the butanol fractions from both cultivars protected primary cultured cortical cells from the oxidative damage induced by H₂O₂ or xanthine and xanthine oxidase, with the BR butanol fraction being more active. The butanol fractions from NC and BR did not produce cytotoxicity in our cultures treated for 24 h at the concentrations of up to 100 μg/ml. Taken together, these results indicate that the leaves of the two cultivars of Perilla frutescens exert antioxidant and neuroprotective effects, and that the butanol fraction from BR leaves exhibits the most potent antioxidative neuroprotection among the fractions tested in this study.